2022
DOI: 10.2174/1570159x20666220624111855
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and its Role in the Alcohol Abuse Initiated During Early Adolescence: Evidence from Preclinical and Clinical Studies

Abstract: Brain-derived neurotrophic factor (BDNF) is a crucial brain signaling protein that is integral to many signaling pathways. This neurotrophin has shown to be highly involved in brain plastic processes such as neurogenesis, synaptic plasticity, axonal growth, and neurotransmission, among others. In the first part of this review, we revise the role of BDNF in different neuroplastic processes within the central nervous system. On the other hand, its deficiency in key neural circuits is associated with development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 294 publications
0
5
0
Order By: Relevance
“…At present, there is some evidence that the expression of hippocampal brain-derived neurotrophic factor (BDNF), a factor that regulates the survival and differentiation of newborn neurons, is suppressed and neurogenesis is interrupted by alcohol use during adolescence. Interestingly, neurogenesis impairment and depression-like symptoms induced by repeated alcohol use in adolescence are reversed after BDNF agonist administration during alcohol withdrawal and abstinence [115], indicating that alcohol likely interrupts adult neurogenesis via the suppression of hippocampal BDNF expression. Chronic binge-like alcohol consumption during adolescence also causes persistent neural and behavioral alterations due to the induction of neuroinflammation [116].…”
Section: Alcohol and Stressmentioning
confidence: 99%
“…At present, there is some evidence that the expression of hippocampal brain-derived neurotrophic factor (BDNF), a factor that regulates the survival and differentiation of newborn neurons, is suppressed and neurogenesis is interrupted by alcohol use during adolescence. Interestingly, neurogenesis impairment and depression-like symptoms induced by repeated alcohol use in adolescence are reversed after BDNF agonist administration during alcohol withdrawal and abstinence [115], indicating that alcohol likely interrupts adult neurogenesis via the suppression of hippocampal BDNF expression. Chronic binge-like alcohol consumption during adolescence also causes persistent neural and behavioral alterations due to the induction of neuroinflammation [116].…”
Section: Alcohol and Stressmentioning
confidence: 99%
“…The association between alcohol consumption and BDNF levels has gained substantial attention due to its potential implications for understanding the neurobiological effects of alcohol on brain health 8 . Preclinical studies have demonstrated that alcohol exposure can modulate BDNF expression, leading to alterations in neuronal plasticity and impairments in cognitive functions 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The association between alcohol consumption and BDNF levels has gained substantial attention due to its potential implications for understanding the neurobiological effects of alcohol on brain health 8 . Preclinical studies have demonstrated that alcohol exposure can modulate BDNF expression, leading to alterations in neuronal plasticity and impairments in cognitive functions 8 , 9 . Additionally, clinical studies have provided evidence of BDNF dysregulation in individuals with alcohol use disorders, further highlighting the importance of investigating the relationship between alcohol and BDNF levels 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants oen impact BDNF levels, inuencing neuroplasticity and neuronal survival through TrkB receptors. 29 These receptors and associated neurotransmitter systems are targeted by various classes of antidepressants, collectively impacting mood, emotions, and brain function to alleviate symptoms of depression. 30,31 Metal-catalyzed transformations have been employed in the synthesis of antidepressants at several sites along the pathway, leading to the development of C-C, and C-N bonds and the functionalization of aromatic rings.…”
mentioning
confidence: 99%
“…Antidepressants often impact BDNF levels, influencing neuroplasticity and neuronal survival through TrkB receptors. 29 These receptors and associated neurotransmitter systems are targeted by various classes of antidepressants, collectively impacting mood, emotions, and brain function to alleviate symptoms of depression. 30,31…”
mentioning
confidence: 99%